تقييم النتائج العلاجية لداء هودجكن - جرجس, ميخائيل; جالق, رياض; ماوردي, أسامة علي (Latakia University Journal -Medical Sciences Series, 2019)
داء هودجكن ورم لمفي خبيث قابل للشفاء، ذو خصائص سريرية ومخبرية ونسيجية مميزة [1]. أول من وصف المرض كان Thomas Hodgkin عام 1832م [2]. يشخص سنوياً في الولايات المتحدة الأمريكية 2-3 حالات لكل 100000 نسمة، وهو يشكل 0.7% من الخباثات [1]. يتم معالجة المرضى بالمعالجة الشعاعية و/أو الكيماوية بناءً على مرحلة الورم وعوامل سوء الانذار [3]. يهدف هذا البحث إلى تسليط الضوء على هذا المرض، وإعطاء فكرة عن النتائج العلاجية التي تم الحصول عليها في محافظتنا، وبالتالي محاولة تحديد سبب عدم الاستجابة والنكس، آملين تحسين نسبة الشفاء قدر الإمكان. أجري البحث بالطريق الراجع على (41) مريض داء هودجكن والذين يعالجون في مشفى الأسد الجامعي باللاذقية والوحدات المهنية التابعة لها بين عامي 1998-2003، وذلك بالعودة إلى أضابيرهم ومراجعة كافة الاستقصاءات والاجراءات المتخذة لديهم، ومن ثم متابعة نتائج معالجة هؤلاء المرضى لمدة سنتين على الأقل. نتائج الدراسة بيّنت: نسبة إصابة الذكور أعلى بقليل من الإناث. ذروة الإصابة بداء هودجكن في دراستنا كانت في العقد الثالث من العمر. ظرف الكشف الأكثر شيوعاً لدى مرضانا هو ضخامة العقد اللمفاوية. ازدياد عدد المرضى الذين يبدون وجود علامات عامة. ارتفاع سرعة التثفل لدى عدد كبير من المرضى. فقر الدم المشاهد لدى مرضى الدراسة كان من نمط سوي الحجم – سوي الصباغ (10 مرضى)، وناقص الحجم – ناقص الصباغ (7 مرضى)، وانحلالي مناعي ذاتي (مريض واحد). وجود إصابة بالعقد اللمفاوية المنصفية لدى أكثر من نصف المرضى. ارتفاع عدد المرضى ذوي المراحل السريرية المتقدمة. كان معدل الاستجابة على المعالجة لدى الإناث أعلى منه لدى الذكور. كان معدل الاستجابة على المعالجة لدى الشباب أعلى منه لدى الأطفال والمسنين. كان معدل الاستجابة على المعالجة لدى المرضى ذوي النمط النسيجي غلبة اللمفاويات أعلى منه لدى المرضى ذوي الأنماط النسيجية الأخرى. كان معدل الاستجابة على المعالجة لدى المرضى ذوي المراحل I، II أعلى منه لدى المرضى ذوي المراحل III، IV. Hodgkin disease (HD) is a curable malignant lymphoma with distinct clinical, biological and histological characteristics [1]. Thomas Hodgkin first described HD in 1832 [2]. In U.S.A: The age – adjusted incidence rate is 2-3 cases per 100.000 individuals (about 0.7% of all cancers) [1]. Patients with HD are treated by radiotherapy or/and chemotherapy according to the stage and adverse prognostic factors [3]. The purpose of this research is to focus on this disease, and to give an idea about therapeutical results we had achieved in our city, there – by trying to know the causes of resistance and relapse, then improve rates of treatment. A retrospective research was undertaken. About (41) patients have been treated in Al-Assad University Hospital in Lattakia and its clinical units between 1998-2003, by returning to their records, and looking up all examinations and investigations that had been made for them. And following their therapeutical results for two years in minimum. The results of research showed: Incidence rate was a little more higher in males than in females. Age-specific incidence rate has a peak in the third decade. Lymphadenopathy was the most common diagnostic circumstance in our research. Number of patients with general signs was high. Erythrocyte sedimentation rate (ESR) is elevated in a large number of patients. Anemia in our research was divided to normocytic – normochromic type (10 patients), microcytic – hypochromic type (7 patients) and autoimmune hemolysis type (1 patient). Mediastinal lymphadenopathy was found in more than 50% of the patients. Number of patients with advanced-stage disease was high. Response rate in females was higher than in males. Response rate in young adults was higher than in children and older individuals. Response rate in patients with lymphocytic predominance was higher than other histological types. Response rate in patients with stage I, II was higher than in patients with stage III, IV.